Faster, higher, smarter : bright ideas that transformed sports - Shapiro, Simon (Annick Press, 2016)
Looks at the hard science behind many inventions and improvements in sports. Readers will find out how the introduction of the aluminum bat changed baseball; how a slapshot works, and what's involved in bending a ball like Beckham. It also covers the history of such milestones as the introduction of diversity, disabled athletes, and women in sport.